Asymmetric Decentralization and the Rise of Monitorial Citizens: Institutional Opportunity Structures in Indonesia's Special Autonomy Regions - Cicellia, Celly; Widaningrum, Ambar; Isnadi, Yuli (Journal of Governance and Public Policy, 2026)
Monitorial citizenship is a model of citizenship widely regarded as more realistic, yet the literature on it remains dominated by Western countries, thereby neglecting the specific contexts of developing nations. This study analyzes the potential for the development of the “monitorial citizen” by linking it to the context of asymmetric decentralization in Indonesia. Using a qualitative multiple-case study approach with an embedded method across four asymmetric regions (Papua, Aceh, Yogyakarta, and Jakarta), this study fully utilizes secondary data comprising regional democracy indices, the performance achievements of Regional People’s Representative Councils, and relevant regulations. The study’s findings indicated that asymmetric decentralization does not automatically influence the potential for the development of “monitorial citizens.” Variations in institutional configurations across the four case studies confirm this. Four aspects influence the development of citizen monitoring: the quality of regional democracy, the capacity of representative institutions, the availability of complementary participation channels, and the interaction between existing institutions and the public. This study also provides recommendations that emphasize institutional aspects in discourses on citizen monitoring and asymmetric decentralization.